Body shape and risk of glaucoma: A Mendelian randomization - Yuan, Ruolan; Liu, Kangcheng; Cai, Yingjun; He, Fei; Xiao, Xiaoxiong; Zou, Jing (Frontiers in Medicine, 2022)
Background: Body size (BS) is one of the risk factors for the development of many clinical diseases, but the relationship between BS and glaucoma is controversial. Herein, we try to use Mendelian randomization (MR) method to study BS causal association with glaucoma risk from the genetic level. Method: The Body Size was determined through anthropometric traits (ATs), such as body mass index (BMI), waist-to-hip ratio adjusted by body mass index (WHRadjBMI), waist-to-hip ratio (WHR), and waist circumference (WC). Association of single nucleotide polymorphisms (SNPs) with each AT and glaucoma were determined individually from the aggregated data of the Genetic Investigation of Anthropometric Traits (GIANT) consortium and the FinnGen study summary data (8591 cases with glaucoma and 210,201 controls). To explore the role of BS and glaucoma, a two-sample MR analysis was performed on genome-wide association study (GWAS) data. Besides, three MR methods (inverse variance weighted [IVW], weighted median, and MR-Egger regression) were used to get the whole causal estimate for multiple instrumental SNPs. Results: BMI (OR = 1.20; 95%CI = 1.02-1.41; P = 0.03) and WC (OR = 1.32;95%CI =1.04-1.69; P = 0.03) were associated with a risk of glaucoma. Besides, genetically predicted WHRadjBMI (OR = 1.10; 95%CI = 0.85-1.40; P = 0.50) and WHR (OR = 1.22;95%CI=0.91-1.62; P = 0.18) were not associated with glaucoma. No heterogeneity and directional pleiotropy were detected. Conclusion: The data of this study revealed that increased BMI and WC are potential risk factors for glaucoma, and WHRadjBMI and WHR are not associated with the occurrence of glaucoma.